Observability time for the pulsar that moves in external strong gravitational field - Komarov, Stanislav O. (Journal of the Belarusian State University. Physics, 2019)
The problem of propogation of radiation of pulsar that moves in external gravitational field is considered in the article. The relations for the calculation of the intervals of time when the pulsar can not be observed are obtained. The general relativistic effects caused by two different mechanisms are analysed. The first one is determined by the twisted trajectories of light that propogates to the observer, and the second one by the precession of the rotation axis of pulsar due to interaction of the spin angular momentum of the pulsar with external gravitational field. It is shown that the radiation from pulsarthat moves in the vicinity of supermassive black hole can be detected by Earth observer only in certain intervals of time. These intervals can have length of order of the period of pulsar motion aroud the black hole. The possibilities of application of these results to the investigation of the pulsars in the vicinity of the Galactic Center are discussed. The numerical model that gives possibilities for calculating of the time of observability of pulsar for distinct parameters of motion of pulsar is presented. Due to the general relativistic consideration of the problem in this paper it is possible to use our results for the pulsar that is close to a supermassive black hole event horison.
Keywords: extarrnal gravitational field; gravitational lensing; pulsar; Galactic Center